Women's willingness to experiment with condoms and lubricants: A study of women residing in a high HIV seroprevalence area. (March 2018) - Sanders, Stephanie A; Crosby, Richard A; Milhausen, Robin R; Graham, Cynthia A; Tirmizi, Amir; Yarber, William L; Beauchamps, Laura; Mena, Leandro
The objective of this study was to investigate women's willingness to experiment with new condoms and lubricants, in order to inform condom promotion in a city with high rates of poverty and HIV. One hundred and seventy-three women (85.9% Black) sexually transmitted infection clinic attendees in Jackson, Mississippi, United States completed a questionnaire assessing willingness to experiment with condoms and lubricants and sexual pleasure and lubrication in relation to last condom use. Most women were willing to: (1) experiment with new types of condoms and lubricants to increase their sexual pleasure, (2) touch/handle these products in the absence of a partner, and (3) suggest experimenting with new condoms and lubricants to a sex partner. Previous positive sexual experiences with lubricant during condom use predicted willingness. The role women may play in male condom use should not be underestimated. Clinicians may benefit women by encouraging them to try new types of condoms and lubricants to find products consistent with sexual pleasure.